Experimental study of the effect of the concentration of water/polyalkylene glycol solutions on heat transfer in steels subjected to quenching - Brandon Farrera Buenrostro; Constantin Alberto Hernández Bocanegra; José Angel Ramos Banderas; Luis Enrique Molina Valdovinos; Nancy Margarita López Granados; Sami Vapalahti (Materials Research Express, 2024)
In this work, the heat transfer coefficients were determined utilizing an experimental study for cooling a 15B35H boron steel, using aqueous solutions of polyalkylene glycol (PAG) as a cooling fluid. A cooling tank was designed and built to allow the fluid recirculation, where the effect of agitation and the PAG content in a concentration range of 2%–6% vol. were analyzed. The thermal histories of cylindrical probes instrumented with K-type thermocouples were obtained, and the heat transfer coefficients associated with the types of refrigeration were calculated, solving the IHCP. The results show the presence of two maximum surface heat flux denominated q1 _max for the low-temperature range and q2 _max for the high-temperature range. Getting higher q1 _max and low q2 _max is desirable to avoid distortion and cracking. It was found that 4% PAG exhibits a slight variation of heat flux values in both low and high-temperature regions, regardless of the degree of agitation, maintaining values of about 3 MW·m ^−2 for q1 _max and 5.5 MW·m ^−2 for q2 _max . In this case, q2 _max is higher than q1 _max , leading to higher cooling rates in the martensitic transformation zone, increasing the risk of distortion and cracking. In the cases of 2 y 6% PAG, agitation affects q1 _max ranging from 2.5 to 6 MW·m ^−2 , and for q2 _max from 4 to 6 MW·m ^−2 , where q1 _max is always higher than q2 _max , providing better conditions for quenching.